SINDROM EPILEPSI YANG MEMBAIK DENGAN TINDAKAN BEDAH - Aris Catur Bintoro (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION FSOME TYPES OF EPILEPSY HAD POOR RESPONSE TO PHARMACOTHERAPY KNOWN AS INTRACTABLE EPILEPSY PROLONGED PHARMACOTHERAPY AND POSTPONING OTHER ALTERNATIVE THERAPY FOR EPILEPSY WHICH TEND TO BE INTRACTRABLE FREQUENTLY CARRY LESS FAVORABLE EFFECT FOR PATIENTS FURTHER PROGNOSIS